Management of infertility : a practical approach - Lagana, Antonio Simone; Guglielmino, Antonino (Academic Press, 2023)
Management of Infertility: A Practical Approach offers an accurate and complete reference for the management of infertility and a robust step-by-step guide for assisted reproduction technologies (ARTs), including how to plan, design and organize a clinical setting and laboratory. The book also provides an evidence-based, complete and practical description of the available methods for diagnosis and management of male and female infertility. This will be an ideal resource for researchers, students and clinicians who want to gain complete knowledge about both basic and advanced information surrounding the diagnosis and management of infertility and related disorders.